Validating a Standardized Approach to the Taylor Aggression Paradigm. Issue 5 (July 2019) - Chester, David S.; Lasko, Emily N.
The Taylor Aggression Paradigm (TAP) is a frequently used laboratory measure of aggression. However, the flexibility inherent in its implementation and analysis can undermine its validity. To test whether the TAP is a valid aggression measure irrespective of this flexibility, we conducted two preregistered studies (Study 1 n = 177, Study 2 n = 167) of a standardized version of the TAP. Across both studies, TAP scores showed agreement with other laboratory aggression measures, were magnified by an experimental provocation manipulation, and were associated with traits typically linked to aggressive behavior. Mixed evidence was found for the external and discriminant validity of the task. Individual responses largely loaded onto a single component, suggesting that the aggregate scoring approach accurately represents the underlying data structure. These results provide preliminary support for the internal validity of this TAP approach and highlight the utility of preregistration in psychometric research.